+0  
 
0
368
1
avatar+314 

(x-1)(x+2)=70

 

(6x^2-7x)^2-2(6x^2-7x)-3=0

 

9(x-1)^2=4(x-2)^2

 Sep 26, 2017
 #1
avatar+7352 
+2

(x - 1)(x + 2)  =  70

                                      Multiply out the left side of the equation.

x2 + x - 2  =  70

                                      Subtract  70  from both sides of the equation.

x2 + x - 72  =  0

 

Can you think of two numbers add to  1  and multiply to  -72?   →   -8  and  +9 .

So the left side can be factored like this...

 

(x - 8)(x + 9)  =  0           Now we set each factor equal to zero and solve for  x  .

 

x - 8  =  0      or      x + 9  =  0

     x  =  8      or            x  =  -9

 

-------------------

 

I don't know the best way to do the second one, but I'm sure someone else on here does.

Here's the third one:

 

9(x - 1)2  =  4(x - 2)2     Take the ± square root of both sides.

                                     (We only need to write the ± on one side though.)

 

\(\sqrt{9(x-1)^2}\,=\,\pm\sqrt{4(x-2)^2} \\~\\ \sqrt9\cdot\sqrt{(x-1)^2}\,=\,\pm\sqrt4\cdot\sqrt{(x-2)^2} \\~\\ 3(x-1)\,=\,\pm2(x-2) \)

 

\(3x-3\,=\,\pm(2x-4)\)       Split this into two seperate equations.

 

\(\begin{array} \ 3x-3=+(2x-4)\qquad\text{or}\qquad&3x-3=-(2x-4) \\~\\ 3x-3=2x-4&3x-3=-2x+4 \\~\\ x-3=-4&5x-3=4 \\~\\ x=-1&5x=7 \\~\\ &x=\frac75 \end{array}\)

.
 Sep 27, 2017

13 Online Users

avatar
avatar